Prevalence of diabetes and prediabetes in South Asian countries: A systematic review and meta-analysis - Ali, Masum; Alam, Md Mahbub; Rifat, M. A.; Simi, Sonjida Mesket; Sarwar, Sneha; Amin, Md Ruhul; Saha, Sanjib (Springer, 2025)
Introduction South Asia is observing an epidemiological transition from communicable to non-communicable diseases where diabetes is an important marker. In this study, we estimate the overall prevalence of diabetes and prediabetes in South Asian countries.